Differences in the acute inflammatory and glucose regulatory responses between small-sided games and cycling in sedentary, middle-aged men. Issue 6 (November 2015) - Mendham, Amy E.; Duffield, Rob; Marino, Frank; Coutts, Aaron J.
Abstract: Objectives: This study compared the acute inflammatory and glucose regulatory response within and between rugby specific small-sided games and stationary cycling in sedentary, middle-aged Caucasian men. Design: Nine middle-aged, sedentary men who were free from disease participated in 2 × 40 min exercise conditions (stationary cycling and small-sided games) in a randomised, cross-over design. Methods: Heart rate and Rating of Perceived Exertion were collected during each bout. Venous blood was collected at fasting, 0, 30, 60 and 240 min post-exercise for measurement of glucose, insulin, cortisol and inflammatory markers including tumour necrosis factor-α, interleukin-1β, interleukin-6, interleukin-1 receptor agonist and C-reactive protein. Results: No significant differences existed between conditions for heart rate and Rating of Perceived Exertion ( p > 0.05). Interleukin-6 was increased immediately post-exercise in both conditions ( p < 0.05), but greater in small-sided games at 240 min post-exercise compared with stationary cycling ( p < 0.05). Glucose was lower in small-sided games than stationary cycling at 30 and 240 min post-exercise ( p < 0.05). Interleukin-1receptor agonist, insulin and cortisol showed an exercise-induced increase ( p < 0.05), with no significant differences between conditions ( p > 0.05). Results for C-reactive protein, tumour necrosis factor-α and interleukin-1β showed no significant exercise-induced changes within or between conditions ( p > 0.05). Conclusions: Both small-sided games and stationary cycling conditions were sufficient to stimulate an acute anti-inflammatory response as indicated by the post-exercise elevation of interleukin-6, interleukin-1receptor agonist and cortisol. The novel findings are that an acute bout of small-sided games bout is capable of maintaining an elevated post-exercise interleukin-6 response and lowered blood glucose concentration, compared with intensity- and duration-matched stationary cycling condition.